Durability and shrinkage of concrete with CDW as recycled aggregates: Benefits from superplasticizer's incorporation and influence of CDW composition. (20th April 2018) - Bravo, M.; de Brito, J.; Evangelista, L.; Pacheco, J.
Highlights: Superplasticizers as a means to produce durable recycled aggregates concrete. Effect of recycled aggregates composition and incorporation ratio on concrete. Comparison of concrete with and without superplasticizer. Recycled aggregate characteristics limit the efficiency of superplasticizers. Superplasticizers improve durability except when chloride ingress is a concern. Abstract: The shrinkage and durability properties of a total of 34 concrete mixes with recycled aggregates produced from different untreated construction and demolition waste (CDW) were tested. The effect of a polycarboxylic superplasticizer on the enhancement of these properties is presented, discussed, and compared with the findings of studies on concrete whose recycled aggregates are sourced from concrete. All properties were significantly affected by recycled aggregate incorporation and this effect was strongly dependent on the properties of the recycled aggregates of each specific source. The superplasticizer was less efficient in mixes with CDW than when the recycled aggregates were produced from concrete, the most common source of recycled aggregates in experimental works, despite untreated CDW being more practical and desirable from an industrial and environmental perspective.